Barriers and Facilitators of Compliance to HIV Counseling and Testing Among Healthcare Workers and Pregnant Women: A Mixed-Methods Study - Pineda, Mark Jeembs; Toledo, Fauline Joy; Cruel, Maria Salve; Dela Cruz, Jenine Nicole; Edralin, Rae Jerbie; Fonte, Sharra Mae; Galamiton, Lore Mae; Genavia, Jesper Ryan; Pastrana, Trisha Nelleane; Tanjuatco, Patricia Marie; Verana, Ron Rowan (Journal of Interdisciplinary Perspectives, 2025)
HIV counseling and testing (HCT) is a cornerstone of prenatal care for preventing mother-to-child transmission (PMTCT). However, compliance and adherence remain inconsistent in the Philippines despite national policies mandating provider-initiated counseling and testing (PICT). This study assessed the compliance and adherence of healthcare workers (HCWs) and pregnant women to HCT in a Department of Health (DOH)-retained hospital, evaluated their knowledge, attitudes, and practices (KAP), and identified influencing factors to inform strategies that strengthen PMTCT services. An explanatory sequential mixed-methods design was employed at Tondo Medical Center. Quantitative data were collected from 37 HCWs via total enumeration and from 385 pregnant women via simple random sampling. In comparison, qualitative data were collected through focus group discussions (FGDs) with 3 HCWs and 12 pregnant women until thematic saturation was reached. Data were analyzed using descriptive statistics, chi-square and eta correlation tests, and thematic analysis guided by grounded theory. Results showed that 81.1% of HCWs performed HCT during prenatal care, but only 59.5% did so postnatally. Among pregnant women, 64.2% underwent prenatal screening, 18.7% postnatal screening, and 12.5% had no screening. HCWs exhibited high knowledge (M = 4.18), positive attitudes (M = 4.21), and good practices (M = 4.09), while pregnant women showed moderate knowledge (M = 3.42) but positive attitudes (M = 4.02). Significant associations were found between HCWs’ knowledge and practices (η = 0.41, p = .041) and between women’s education (p = .032), income (p = .018), and HCT adherence. Qualitative findings revealed barriers such as stigma, fear, and workload, as well as facilitators such as empathy, rapport, and education. Strengthening PICT integration, enhancing HCW training, reducing stigma, and institutionalizing structured postnatal follow-up are recommended to improve adherence and maternal and child health outcomes.